Sun, Sex, and Style in Smart Cinema: Tilda Swinton in A Bigger Splash (Luca Guadagnino, 2015). (2nd November 2017) - Gilligan, Sarah
Abstract: This article will examine the ways in which costuming plays a pivotal and disruptive role in A Bigger Splash . Through Tilda Swinton's virtually mute performance as recovering rock star Marianne Lane, the intersections between clothing, the body, and performance construct a visual language dominated by desire, touch, conflict, turmoil, and disguise. With costumes designed by Raf Simons at Dior, in collaboration with Giulia Piersanti, an aesthetic of stylish resort wear is showcased to a niche audience. Although A Bigger Splash attempts to position itself as a European version of the American "smart film, " I will argue that it is a "Euro-pudding": a well-intentioned European coproduction with transnational scope, that aspires to art film status, but is devoid of broader social or political resonance. Through the casting of Swinton, ambivalence is commodified and used to promote luxury designer fashion to an aspirational audience rich in cultural capital, that wishes to distance itself from mainstream celebrity culture and Hollywood blockbusters.